Condition and Prospects of Development of Vaccines for Specific Prevention of Enterovirus (Nonpolio) Infection - E. A. Yagovkin; G. G. Onishchenko; A. Yu. Popova; E. B. Ezhlova; A. A. Melnikova; M. Yu. Soloviev; E. V. Kovalev; T. I. Tverdokhlebova; G. V. Khmelevskaya; L. V. Devterova; B. F. Vachaev; I. L. Yuryeva (Эпидемиология и вакцинопрофилактика, 2016)
This review summarizes the material on the development of vaccines against (nonpolio) enterovirus infection in Russia and abroad. Described the developed vaccine types, their characteristics and the results of clinical and epidemiological trials, created in China inactivated vaccines. I’is considered the possibility of creating a mucosal vaccines and vaccinal prevention strategies.